Pemanfaatan Cerita Pendek “The Crab Trap” sebagai Media Identifikasi Kalimat Perintah di Sekolah Dasar - Putri, Elsa Ika; Ardanti, Devara Yogiska; Kholifah, Suci Nur; Almalia, Virli; Widagdo, Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines how command sentences are used in the short story “The Crab Trap” to help elementary school students learn language. This study uses a literature study method with a descriptive qualitative approach that aims to analyze findings from various national and international journals related to the application and development of language learning through children’s literature media. This study examines various types of command sentences found in the story “The Crab Trap”. The findings of the study show that the command sentences in the story serve various purposes and have different forms, which reflect how language is used in real-world communication. The use of command sentence analysis in the short story “The Crab Trap” can enhance language learning strategies in elementary schools by providing students with contextualized and meaningful examples of language use and enhancing their understanding of the relationship between language structure and social interaction.